2015
DOI: 10.1007/s40264-015-0308-6
|View full text |Cite
|
Sign up to set email alerts
|

Accidents and Incidents Related to Intravenous Drug Administration: A Pre–Post Study Following Implementation of Smart Pumps in a Teaching Hospital

Abstract: We observed no risk reduction associated with the implementation of smart pumps in a 500 bed mother-child hospital. Further studies are required to explore the details of the potential risk reduction associated with the use of smart pumps.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(32 citation statements)
references
References 30 publications
(38 reference statements)
1
31
0
Order By: Relevance
“…45 Accurate weight scales that only measure in metric units (kilograms or grams), 87 standardized equipment throughout a system, drug dose range limits, programmable "smart" infusion pumps for hospitals, and standardized order sets should be used. 88,89 Drug shortages have recently become an additional safety risk. 90 Clinical pharmacists who are trained in pediatrics are invaluable for medication reconciliation (especially for high-risk children) and may be integrated into inpatient rounds and used for the education of staff and families in all settings as often as possible.…”
Section: Patient Safety Goals and Effortsmentioning
confidence: 99%
“…45 Accurate weight scales that only measure in metric units (kilograms or grams), 87 standardized equipment throughout a system, drug dose range limits, programmable "smart" infusion pumps for hospitals, and standardized order sets should be used. 88,89 Drug shortages have recently become an additional safety risk. 90 Clinical pharmacists who are trained in pediatrics are invaluable for medication reconciliation (especially for high-risk children) and may be integrated into inpatient rounds and used for the education of staff and families in all settings as often as possible.…”
Section: Patient Safety Goals and Effortsmentioning
confidence: 99%
“…Therefore, our findings need to be confirmed in multiple hospital settings, to enable generalization, and more studies of IPISs are needed. In most countries where IV preparation errors were reported, ready-to-use IV bags, eMARs, and smart pumps with bar codes are not in common use yet [12,13,[22][23][24][25][48][49][50][51][52][53][54]. However, these systems will likely be implemented in the future.…”
Section: Study Limitationmentioning
confidence: 99%
“…Some studies have demonstrated smart pump technology has intercepted potentially serious medication errors, significantly decreased reported errors and reduced costs associated with IV infusions . Other studies have shown no meaningful reduction in serious medication error rates since the implementation of smart pumps …”
Section: Introductionmentioning
confidence: 99%